Transmission electron microscopy investigation of a porphyrin-containing organic-inorganic hybrid nanomaterial - Taranu Bogdan-Ovidiu (Proceedings of the International Symposium on Analytical and Environmental Problems, 2024)
An organic-inorganic hybrid nanomaterial containing the A3B-type free-base porphyrin 5-(4- carboxyphenyl)-5,10,15-tris(4-phenoxyphenyl)-porphyrin, the polysaccharide k-carrageenan and Fe3O4 magnetic nanoparticles was successfully synthesized and analyzed using Transmission Electron Microscopy (TEM). Different operating modes – TEM Bright Field, High-Resolution TEM and Scanning Transmission Electron Microscopy – were employed during the investigation. The recorded images provide morphological and structural data concerning the detailed understanding of the hybrid in ways that are specific to the aforementioned characterization technique. The results of the study complement the scientific knowledge relevant to domains of current interest for researchers, such as porphyrin chemistry and the nanomaterials field.